PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN MOTIVASI KERJA GURU TERHADAP PENINGKATAN KINERJA GURU PPPK DI SD NEGERI SE KECAMATAN SAKO PALEMBANG - Dwi Prabuyanti; Syarwani Ahmadi; Nila Kesumawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of work motivation and teacher work motivation on improving PPPK teacher performance in State Elementary Schools in Sako District, Palembang. This type of research is quantitative research using an expost facto research design. The sample in this study was 157 State Elementary School teachers in Sako District, Palembang. The data collection technique used a questionnaire. The data analysis technique used quantitative descriptive analysis techniques and multiple regression. The results of this study state that: There is a significant influence of principal leadership on PPPK teacher performance in State Elementary Schools in Sako District, Palembang and There is a significant influence of work motivation on the performance of PPPK teachers in Public Elementary Schools throughout Sako District, Palembang and There is a significant influence of principal leadership and work motivation together on the performance of PPPK teachers in Public Elementary Schools throughout Sako District, Palembang.